The combined impact of redcedar encroachment and climate change on water resources in the Nebraska Sand Hills - Kishawi, Yaser; Mittelstet, Aaron R.; Adane, Zablon; Shrestha, Nawaraj; Nasta, Paolo (Frontiers in Water, 2022)
The Nebraska Sand Hills (NSH) is considered a major recharge zone for the High Plains Aquifer in the central United States. The uncontrolled expansion of the eastern redcedar (Juniperus Virginiana) under climate warming is posing threats to surface water and groundwater resources. The combined impact of land use and climate change on the water balance in the Upper Middle Loup River watershed (4,954 km2) in the NSH was evaluated by simulating different combinations of model scenarios using the Soil Water Assessment Tool (SWAT) model. A total of 222 climate models were ranked according to the aridity index and three models representing wet, median (most likely), and dry conditions were selected. Additionally, the impacts of carbon dioxide (CO2) emissions on root water uptake were simulated. Four plausible redcedar encroachment scenarios, namely 0.5% (no encroachment), 2.4%, 4.6%, and 11.9%, were considered in the numerical simulations. We, therefore, built: i) the historical scenario (2000-2019) with the current climate and redcedar cover leading to baseline results; ii) the most-likely future scenario (2020-2099) with projected climate (50th percentile of aridity index distribution) and redcedar encroachment that was estimated by using a combination of neural network and Markov-chain cellular automata model; iii) 16 future scenarios (2020-2099) with different combinations of extreme climate (5th and 95th percentiles of aridity index distribution) and four hypothetical encroachment scenarios (0.5%, 2.4%, 4.6%, and 11.9%). The most-likely climate projection indicates that a warming pattern will be expected with a 4.1oC increase in average over the 100-year period, and this will be associated with lower-than-normal precipitation (P). Nevertheless, the concurrent increase in temperature and CO2 concentration is likely to induce stomata closure by reducing potential (ETp) and actual (ETa) evapotranspiration losses. Projected P, ETp, ETa, and discharge (D) are expected to decrease by 6%, 39%, 24%, and 2%, respectively, while recharge (R) will likely increase by 27%. Finally, a sensitivity analysis of 16 combined climate and land use scenarios is presented and discussed. The scenario modeling approach presented in this paper can support decision-making by stakeholders for optimal management of water resources.